Psichofiziologiceskie sostojanija fechtoval'šcic-rapiristok v sorevnovanii - Rodionova, I. A. (Vestnik Moskovskogo gorodskogo pedagogiceskogo universiteta. Serija «Estestvennye nauki», 2016)
In the process of psychological support of competitively-training preparation of female foil fencers is required "fine" diagnosis of psycho-physiological state of athletes. The article describes the results of a comprehensive study conducted with the female foil fencer team of Moscow and Russia, as well as the fencing clubs of capital.